If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + -9 = -14 Reorder the terms: -9 + -5x = -14 Solving -9 + -5x = -14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -5x = -14 + 9 Combine like terms: -9 + 9 = 0 0 + -5x = -14 + 9 -5x = -14 + 9 Combine like terms: -14 + 9 = -5 -5x = -5 Divide each side by '-5'. x = 1 Simplifying x = 1
| 1/10r=41/2 | | 3x-5x=-10-20 | | 2-x=3x+6 | | (p^2-4p-21)/(p^2-2p-35) | | 2/7r=6 | | X+x=10-2 | | 4x=136+9x | | 9-10x=83-24x | | 31x+21x=21 | | 4x+3x=10+4 | | 10=4*T*20/100 | | -64x^2+104x= | | 4x+x+20=200 | | 4/3r=31/2 | | 28=4-3p | | -43-4=7-9x | | x+x+20=200 | | 3p-5=-20 | | 2.4x=8.64 | | 7x^2+16x-15= | | 72-6x=21x+24 | | 7x+1=-35 | | 3x+47=-5 | | 49r(2)+21r=-2 | | 1-6x=-35 | | (2/3)-0,2x=(1/3)-0,5x | | 2c+6=-1-3c | | 70+30=2x | | 3n^2+6n-24=0 | | 5m^2-50m+125=0 | | 6-(1/3)x=2x-3 | | 5(a-8)+14=3(a-6) |